2018
DOI: 10.1016/j.jcrimjus.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Personality functioning and psychopathic traits in child molesters and violent offenders

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research-You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 80 publications
0
6
1
Order By: Relevance
“…Previously, it has been argued that sexual violence and non‐sexual violence to some extent constitute distinct types of aggression (Garofalo et al., 2018; Lussier, 2005; Lussier & Cale, 2013; Mitchell & Beech, 2011; Pettersen et al., 2016), but our findings suggest that aggression measures are unlikely to be helpful as indicators of risk of most sexual offending. In our study, sexual offences could be discriminated from all measures of aggression through a small but consistent negative correlation.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Previously, it has been argued that sexual violence and non‐sexual violence to some extent constitute distinct types of aggression (Garofalo et al., 2018; Lussier, 2005; Lussier & Cale, 2013; Mitchell & Beech, 2011; Pettersen et al., 2016), but our findings suggest that aggression measures are unlikely to be helpful as indicators of risk of most sexual offending. In our study, sexual offences could be discriminated from all measures of aggression through a small but consistent negative correlation.…”
Section: Discussioncontrasting
confidence: 65%
“…Violent offences (including attempted and aggravated forms) were defined as any of the following: homicide, manslaughter, assault, robbery, threats and violence against an officer, gross violation of a woman's or an individual's integrity, unlawful coercion, unlawful threat, kidnapping, illegal confinement and arson. Sexual offences, in some research included as violent offences, were excluded from our variable ‘violent offences’ as there is evidence that they may have a partially different aetiology (Garofalo, Bogaerts & Denissen, 2018; Lussier, 2005; Lussier & Cale, 2013; Mitchell & Beech, 2011; Pettersen, Nunes & Cortoni, 2016). Thus, sexual offences (including attempted and aggravated forms) were coded as a separate variable.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Schimmenti et al, 103 found that child sexual abusers scored higher on the PCL-R than non-violent sex offenders but did not differentiate between child molesters and pedophiles. Another recent study found that violent offenders had higher degrees of psychopathy than child molesters, 104 however the general comparison of "child molesters" to violent non-sex offenders appears less relevant. The authors admit that they included any sex offender who sexually molested a child as "child molesters" and did not differentiate pedophiles from child molesters, including all sex offenders with child victims as child molesters (personal communication with Garofalo, 12/31/2018).…”
Section: Psychopathy Among Sex Offendersmentioning
confidence: 94%
“…Other investigators have successfully proposed the addition of new items to improve the psychometric performance of the LSRP in general, and of the Callousness scale in particular (Christian & Sellbom, 2016). However, considering that the original LSRP is still vastly used worldwide, thanks to its availability in several languages (Chabrol, Labeyrie, Rodgers, & Levenson, 2010;Garofalo, Bogaerts, & Denissen, 2018;Shou et al, 2017;Somma et al, 2014;Uzieblo, Verschuere, & Crombez, 2006;Verschuere et al, 2014;Wang et al, 2018), further scrutiny of the model fit and construct validity of the three-factor structure of the LSRP seems warranted, before its use can be discouraged. For instance, in a recent study, the Chinese translation of the LSRP has yielded promising results in terms of measurement invariance and construct validity of its three-factor structure (Shou et al, 2017), hence renovating its status as an efficient self-report measure of psychopathic traits.…”
mentioning
confidence: 99%